Deciphering the virulence factors, regulation, and immune response to Acinetobacter baumannii infection - Shadan, Afreen; Pathak, Avik; Ma, Ying; Pathania, Ranjana; Singh, Rajnish Prakash (Frontiers in Cellular and Infection Microbiology, 2023)
Deciphering the virulence factors, regulation, and immune response to Acinetobacter baumannii infectionAcinetobacter baumannii is a gram-negative multidrug-resistant nosocomial pathogen and a major cause of hospital acquired infetions. Carbapenem resistant A. baumannii has been categorised as a Priority1 critial pathogen by the World Health Organisation. A. baumannii is responsible for infections in hospital settings, clinical sectors, ventilator-associated pneumonia, and bloodstream infections with a mortality rates up to 35%. With the development of advanced genome sequencing, molecular mechanisms of manipulating bacterial genomes, and animal infection studies, it has become more convenient to identify the factors that play a major role in A. baumannii infection and its persistence. In the present review, we have explored the mechanism of infection, virulence factors, and various other factors associated with the pathogenesis of this organism. Additionally, the role of the innate and adaptive immune response, and the current progress in the development of innovative strategies to combat this multidrug-resistant pathogen is also discussed.